Artificial Intelligence in English as a Foreign Language Learning: A Study of Its Impact on Teaching and Learning Processes - Aditia, Laura; Ulantari, Okta; Wahyuni, Sri (Journal of English Language and Education, 2026)
This study discusses how Artificial Intelligence (AI) is used in learning English and how it influences the teaching and learning process as a whole. Based on a library research, various AI tools such as chatbots, chat gpt, and adaptive learning applications can provide instant feedback and adjust lessons according to each student’s ability. The findings show that AI helps improve students’ motivation, communication skills, and learning efficiency. However, there are still challenges, including limited technology, unequal access to digital resources, and students becoming overly dependent on automation. Therefore, AI should be implemented in education ethically and collaboratively to support teachers and maintain a balance between technology and human interaction. AI tools like chatbots, personalized learning apps, and language processing software assist students in practicing English by giving quick feedback and adjusting to their learning pace (Rohmiyati, 2025, p. 8). Moreover, the use of AI technology provides significant benefits for teachers in addressing challenges in the digital era